2017
DOI: 10.1093/jscr/rjx212
|View full text |Cite
|
Sign up to set email alerts
|

A case of Mirizzi syndrome that was successfully treated by laparoscopic choledochoplasty using a gallbladder patch

Abstract: The use of laparoscopic surgery in the treatment of Mirizzi syndrome is considered controversial due to the degree of technical difficulty. We herein describe the case of a 36-year-old woman who was admitted to our hospital due to appetite loss, nausea and back pain. Endoscopic retrograde cholangiography revealed a round-shaped filling defect at the confluence of the bile duct. The patient was diagnosed with Mirizzi syndrome Type II according to the Csendes classification. Before surgery, an endoscopic nasobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…ERBD tube replacement may thus be useful as a landmark of the common bile duct during surgery. If the ENBD tube could be easily replaced, intraoperative cholangiography would be more helpful for obtaining information on the passage of the bile duct and bile leakage [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERBD tube replacement may thus be useful as a landmark of the common bile duct during surgery. If the ENBD tube could be easily replaced, intraoperative cholangiography would be more helpful for obtaining information on the passage of the bile duct and bile leakage [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 b). Regarding Mirizzi syndrome type II, recent reports have shown the successful completion of laparoscopic surgery, including partial resection and choledochoplasty [ 12 , 17 ]. The surgical procedure should be determined based on the proficiency in laparoscopic surgery of each facility.…”
Section: Discussionmentioning
confidence: 99%
“…Ligamentum teres hepatis (LTH), also known as the round ligament of the liver, as well as the gallbladder flap, have been proposed as suitable autologous tissues for bile duct reconstruction due to their proximity to the biliary system and their potential for regeneration. Previous studies have shown promising results, indicating their viability for repairing bile duct injuries and defects [ [1] , [2] , [3] ].…”
Section: Introductionmentioning
confidence: 99%
“…Mirizzi syndrome (MS) is a rare but well‐described complication of cholelithiasis where an impacted stone in the cystic duct or gallbladder neck causes extrinsic compression of the common hepatic duct (CHD) resulting in obstructive jaundice . We present the case of a woman with type III MS repaired with a novel method of choledochoplasty.…”
mentioning
confidence: 99%